Multicultural Learning Practices for BIPA Learning in Vietnam - Ho Ngoc Hieu; Andriyana (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2025)
Multiculturalism is crucial for foreign speakers (BIPA) in Indonesian language learning, enhancing linguistic competence and intercultural understanding. This study examines multicultural teaching practices in Vietnam, emphasizing music, crafts, culinary arts, dance, and cultural festivals. Using a descriptive qualitative approach with documentation and literature review, the study reveals how traditional arts support language learning. Instruments like gamelan and angklung help students grasp vocabulary through rhythm and collaboration. Painting wooden masks introduces the concept of color philosophy, while Indonesian dishes like tumpeng teach language through culinary processes and cultural meanings. Traditional dances such as saman and piring promote understanding of cooperation and stage confidence. At the University of Social Sciences and Humanities (USSH), multicultural festivals offer international students firsthand experiences with Indonesian culture through performances and exhibitions. The findings highlight that integrating cultural elements into BIPA enhances student engagement and intercultural skills. Embedding Indonesian cultural practices in language instruction creates a more immersive and meaningful learning environment. Ultimately, this multicultural approach strengthens language acquisition and deepens appreciation of Indonesian culture, supporting the development of global communication skills. Participatory and creative methods are key to enriching BIPA learners' understanding of Indonesia's cultural diversity.